If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(y-2)=-5y-14
We move all terms to the left:
-8(y-2)-(-5y-14)=0
We multiply parentheses
-8y-(-5y-14)+16=0
We get rid of parentheses
-8y+5y+14+16=0
We add all the numbers together, and all the variables
-3y+30=0
We move all terms containing y to the left, all other terms to the right
-3y=-30
y=-30/-3
y=+10
| -5x-2=30.5 | | -16+32+28+4m=4(16m+4) | | 3+25=15x+19 | | 64+2x=25-11x | | 1+2x=-3+16x | | 12=2t+10 | | 11x=-48 | | 3(x−2)=2(x+9) | | 2/3(n+2)=3/5 | | 4+|2x+1|=7 | | 0.05=x/5.984 | | 6(6-4k)+6k=90 | | 1.2x+4.8=2.1-x | | 2(2a-7)=14 | | 3x+x+8=36 | | 50-2x+x=180 | | 4x/7=21-3x | | 0.05=y/5.984 | | 2q+8=21 | | 10x-100+5=10x-100 | | 2x+4/3=5x+3/4 | | 90+x=(3x+2) | | 1.4×x=84 | | 1.4×y=84 | | 0.05=5.984/y | | 9.6x−15.4=−4.4x−11.2 | | 7/2p-4=10 | | 0.238095=4/y | | x-3(3/7)=(2/3) | | 3x+1+2x+x=180 | | -9=x/6+x/7 | | F(4)=(1/3)x |